2019
DOI: 10.1016/j.trci.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Vascular retinal biomarkers improves the detection of the likely cerebral amyloid status from hyperspectral retinal images

Abstract: IntroductionThis study investigates the relationship between retinal image features and β-amyloid (Aβ) burden in the brain with the aim of developing a noninvasive method to predict the deposition of Aβ in the brain of patients with Alzheimer's disease.MethodsRetinal images from 20 cognitively impaired and 26 cognitively unimpaired cases were acquired (3 images per subject) using a hyperspectral retinal camera. The cerebral amyloid status was determined from binary reads by a panel of 3 expert raters on 18F-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 53 publications
(65 reference statements)
1
42
0
Order By: Relevance
“…Intriguingly, a similar study from More and colleagues, the team that initially developed the rHSI technique in murine models (More and Vince, 2015;More et al, 2016), found the largest deviation in rHSI signatures between MCI patients and controls, irrespective of other ocular conditions such as cataracts or glaucoma (More et al, 2019). The same technique was able to distinguish cerebral Aβ+ subjects from Aβ− subjects with 85% accuracy based on retinal vascular measures including vessel tortuosity and diameter (Sharafi et al, 2019).…”
Section: Retinal Imagingmentioning
confidence: 88%
“…Intriguingly, a similar study from More and colleagues, the team that initially developed the rHSI technique in murine models (More and Vince, 2015;More et al, 2016), found the largest deviation in rHSI signatures between MCI patients and controls, irrespective of other ocular conditions such as cataracts or glaucoma (More et al, 2019). The same technique was able to distinguish cerebral Aβ+ subjects from Aβ− subjects with 85% accuracy based on retinal vascular measures including vessel tortuosity and diameter (Sharafi et al, 2019).…”
Section: Retinal Imagingmentioning
confidence: 88%
“…1A3), 54 and tunable laser sources (TLS; Fig. 1A3) 30,32,[55][56][57][58][59][60][61][62][63] became more common and enabled narrow-band imaging. The latter is also being used in transluminance and autofluorescence mode on retinal flatmounts.…”
Section: Tunable Wavelength Methodsmentioning
confidence: 99%
“…33,46 LCTF and TLS are among the most used in the history of HSI, with commercially available, ready-to-use imagers on the market. 33,46,47,56,58,59,61,[63][64][65] Less common ways to tune the wavelength output of a device is the acousto-optic tunable filter, where the diffraction of crystals is altered by acoustic waves (Fig. 1A3), 66 and a dual-slit scanning monochromator (Fig.…”
Section: Tunable Wavelength Methodsmentioning
confidence: 99%
See 2 more Smart Citations